PEDAGOGICAL REQUIREMENTS FOR THE PROFESSIONAL TRAINING OF THE PIANO TEACHER - Kurbanov Kuldosh Yuldashevich; Umirova Malika Shavkat qizi (American Journals Publishing, 2023)
Pedagogical requirements and tasks for a piano teacher play an important role in achieving the intended goal. This is reflected in the teacher's qualified expertise, skillful performance, understanding and love of children's psychology.
Keywords: Music, pedagogue, skill, qualification, methods, professional skills, qualified specialist.